SOCIAL ACCOUNTING AND SOCIAL PERFORMANCE MEASUREMENT IN CORPORATE SOCIAL RESPONSIBILITY - Nicholas Renaldo; Achmad Tavip Junaedi; Sudarno Sudarno; Marice Br. Hutahuruk; Luciana Fransisca; Cecilia Cecilia (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Social accounting is necessary for the company as a form of corporate social responsibility towards the environment. In social accounting, it is important to identify social/environmental costs to show the true costs of business inputs and processes and ensure profitability. The social/environmental performance must be measured and evaluated to see if the results achieved are in accordance with what was planned. Social/environmental performance measurement should pay attention to quantitative and qualitative elements, as well as in-process and end-of-process measures so that the measurement system can be optimized.